Voice coil motor, magnetic circuit structural component for the same, and method for manufacturing the same
A VCM with rare earth sintered magnets coated in a multi-layer structure addresses hydrogen embrittlement issues, preventing damage and maintaining magnetic properties for reliable operation in hydrogen atmospheres.
Patent Information
- Application Number
- JP2024027721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-23
- Filing Date
- 2024-02-27
- Publication Date
- 2025-01-09
AI Technical Summary
Voice coil motors (VCMs) used in storage devices like HDDs and tape storages face issues with hydrogen embrittlement when exposed to low-pressure hydrogen atmospheres, leading to damage such as chipping or cracking and deterioration of magnetic properties, which are not adequately addressed by existing technologies.
A voice coil motor with a magnetic circuit component using rare earth sintered magnets coated with a multi-layer structure of metal plating and metal oxide/nitride layers, specifically composed of 28-34% rare earth elements, 2% Co, and additives, with a total coating thickness of 3-80 μm and metal oxide/nitride layer thickness of 0.01-2 μm, to prevent damage and maintain magnetic properties.
The solution effectively prevents chipping, cracking, and deterioration of magnetic properties in VCMs exposed to hydrogen, ensuring precise actuator control and accurate data reading/writing even in hydrogen-filled storage devices.
Smart Images

Figure 2025003290000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a voice coil motor, magnetic circuit components therefor, and a method for manufacturing the same. [Background technology]
[0002] A voice coil motor (hereafter referred to as VCM) is a magnetic circuit component used to drive an actuator in a hard disk drive (hereafter referred to as HDD). Generally, when a HDD is in operation, when a current flows through the coil attached to the actuator, the Lorentz force causes the actuator to move to a specific position on the magnetic media, and the head at the tip of the actuator is used to read and write data on the magnetic media.
[0003] Examples of magnetic media on which data is read and written by a VCM in this way include a circular magnetic disk as described in Patent Document 1, as well as an embedded magnetic tape that is wound and unwound by two reels as described in Patent Document 2. Devices that use an embedded magnetic tape as in Patent Document 2 are called tape storage. In a VCM, when a current is passed through a coil in the magnetic field of a permanent magnet, a force is generated in the coil in a direction perpendicular to the magnetic field, causing the coil to move back and forth.
[0004] On the other hand, as for permanent magnets, Patent Documents 3 and 4 describe rare earth sintered magnets that do not cause hydrogen embrittlement even in a hydrogen atmosphere and can be used in motors, etc., which are composed of 20 to 35 weight % R (R is one or more rare earth elements selected from Nd, Pr, Dy, Tb, and Ho), 15 weight % or less Co, 0.2 to 8 weight % B, 8 weight % or less of at least one element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu, and Zn as an additive, with the balance being Fe and unavoidable impurities, and which are characterized in that a metal oxide layer and / or metal nitride layer is formed on the surface of the rare earth sintered magnet body directly or via n-layer (n is an integer and n≧1) metal plating layers, and a manufacturing method thereof.
[0005] The "motor" described in Patent Document 3 and Patent Document 4 is completely different from a VCM. As described in Non-Patent Document 1, when an electromagnetic diaphragm blower was developed to put hydrogen circulation blowers for fuel cell systems into practical use, the problem was that the parts using permanent magnets in the blower became embrittled in the expected usage environment. At the time Patent Document 3 and Patent Document 4 were filed, research into the supply power of hydrogen fuel was being actively conducted in order to realize a hydrogen energy society, and there was a problem that the permanent magnets mounted on rotary motors deteriorated due to exposure to hydrogen. Patent Document 3 and Patent Document 4 relate to rare earth sintered magnets mounted on such rotary motors. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-140524 A [Patent Document 2] JP 2020-129424 A [Patent Document 3] JP 2003-257721 A [Patent Document 4] JP 2003-257768 A [Non-patent literature]
[0007] [Non-Patent Document 1] NEDOWM (NEDOWeb Magazine), "Development of an innovative blower for fuel cell systems, essential for realizing a hydrogen society," [online], interviewed in November 2016, [Retrieved May 1, 2023], Internet <URL:https: / / webmagazi ne.nedo.go.jp / practical-realization / articles / 201701techno-takatsuki / > Summary of the Invention [Problem to be solved by the invention]
[0008] As described in Patent Document 1 and Patent Document 2, storage devices such as HDDs and tape storages need to fill and seal the inside of their housings with helium in order to suppress vibrations of magnetic heads and magnetic disks. However, due to the rising cost of helium and the desirability of a lower density gas, there is a demand to use hydrogen gas instead of helium. However, as described above, the VCM used in storage devices is equipped with a permanent magnet. As described in Patent Document 3 and Patent Document 4, it has been pointed out that if a permanent magnet is exposed to a high-pressure hydrogen atmosphere for a long period of time, hydrogen embrittlement occurs, causing cracks or powdering of the material.
[0009] When hydrogen is filled into the housing of a storage device such as an HDD, the VCM is placed in a low-pressure hydrogen atmosphere, unlike the rotary motors of Patent Documents 3 and 4. Patent Documents 3 and 4 state that chipping or the like in itself has almost no effect on the magnetic properties of the permanent magnet, and as a comparative example, they merely state that a test sample that does not have the metal oxide layer that is a feature of the invention in those documents was shattered in a 10 MPa hydrogen gas test, but make no mention of any change in the magnetic properties of the permanent magnet exposed to a hydrogen atmosphere.
[0010] The inventors of the present application tested the resistance of permanent magnets to low-pressure hydrogen, assuming that a VCM would be exposed to a low-pressure hydrogen atmosphere for an extended period of time. They were surprised to find that even permanent magnets having only a metal plating layer without a metal oxide layer, which is a characteristic of the inventions described in Patent Documents 3 and 4, did not experience damage such as chipping or cracking to a certain extent, but the magnetic properties of such undamaged permanent magnets deteriorated and they were not suitable for use in a VCM.
[0011] The present invention has been made in consideration of the above problems, and aims to provide a voice coil motor, magnetic circuit components therefor, and a method for manufacturing the same, which can prevent not only damage such as chipping and cracking but also deterioration of magnetic characteristics even when exposed to a low-pressure hydrogen atmosphere for a long period of time. [Means for solving the problem]
[0012] In order to achieve the above object, a voice coil motor, magnetic circuit components therefor, and a manufacturing method thereof according to the present invention are as follows. [1] A magnetic circuit component for a voice coil motor comprising: a pair of yokes; a pair of magnets provided in contact with the inner surfaces of the pair of yokes, respectively; and a support member that fixes the pair of yokes together while maintaining a gap between the pair of magnets, The magnet is a rare earth sintered magnet having a coating on its surface, the rare earth sintered magnet has a composition consisting of 28 to 34 weight % R (R is one or more rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La, and Gd), 2 weight % or less Co, 0.5 to 2 weight % B, 2 weight % or less of at least one element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu, and Zn as an additive, and the balance being Fe and unavoidable impurities; a magnetic circuit component for a voice coil motor, wherein the coating has a multi-layer structure consisting of, in order from the rare earth sintered magnet side, a metal plating layer and a metal oxide layer and / or a metal nitride layer, the metal plating layer further has a multi-layer structure consisting of, in order from the rare earth sintered magnet side, a copper plating layer and a nickel plating layer, the total thickness of the metal plating layer and the metal oxide layer and / or metal nitride layer is in the range of 3 to 80 μm, and the metal oxide layer and / or metal nitride layer has a thickness in the range of 0.01 to 2 μm.
[0013] [2] A voice coil motor comprising the magnetic circuit component for a voice coil motor according to [1] above, and a coil positioned in the gap between the pair of magnets.
[0014] [3] forming a pair of plates made of rare earth sintered magnets having a composition consisting of 28 to 34 weight % R (R is one or more rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La, and Gd), 2 weight % or less Co, 0.5 to 2 weight % B, 2 weight % or less of at least one element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu, and Zn as an additive, and the remainder being Fe and unavoidable impurities; a step of plating the surfaces of the pair of plates with copper and then plating the surfaces with nickel to form a metal plating layer; a step of heat-treating the pair of plates on which the metal plating layer is formed to oxidize and / or nitride the metal of the metal plating layer to form a metal oxide layer and / or a metal nitride layer, in which the total thickness of the metal plating layer and the metal oxide layer and / or the metal nitride layer is in the range of 3 to 80 μm, and the thickness of the metal oxide layer and / or the metal nitride layer is in the range of 0.01 to 2 μm; a step of bonding a pair of yokes to the pair of plates on which the metal oxide layer and / or metal nitride layer is formed, respectively; a step of fixing the pair of yokes to each other with a support member so that the pair of plates bonded to the pair of yokes face each other and a gap is maintained between the pair of plates; A method for manufacturing a magnetic circuit component for a voice coil motor, comprising: Effect of the Invention
[0015] Thus, according to the present invention, a pair of magnets in a magnetic circuit component for a voice coil motor are rare earth sintered magnets with a coating on their surfaces, this rare earth sintered magnet has a predetermined composition, the coating has a multi-layer structure consisting of a predetermined metal plating layer and a metal oxide layer and / or metal nitride layer thereon, the total thickness of the metal plating layer and the metal oxide layer and / or metal nitride layer is within a predetermined range, and the thickness of the metal oxide layer and / or metal nitride layer is within a predetermined range, so that even if the voice coil motor is exposed to a low-pressure hydrogen atmosphere for a long period of time, it is possible to prevent damage to the magnets such as chipping and cracking, and also to prevent deterioration of the magnetic properties of the magnets. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic perspective view showing one embodiment of a magnetic circuit component for a VCM according to the present invention. [Diagram 2] 2 is a schematic front view of the magnetic circuit components of FIG. 1 as viewed from the arrow II. [Diagram 3] FIG. 11 is a schematic perspective view showing another embodiment of a magnetic circuit component for a VCM according to the present invention. [Figure 4] 4 is a schematic front view of the magnetic circuit components of FIG. 3 as viewed from the arrow IV. [Diagram 5] 1 is a graph showing the results of measuring the flux of the sintered magnets of Example 1 and Comparative Example 1. [Figure 6] 2 is a graph showing a demagnetization curve of the sintered magnet of Example 1. [Figure 7] 2 is a graph showing a demagnetization curve of the sintered magnet of Comparative Example 1. [Figure 8] FIG. 1 is a schematic cross-sectional plan view showing magnetic circuit components and torque measurement components for a VCM to explain torque measurement. [Figure 9]FIG. 9 is a schematic cross-sectional side view of the magnetic circuit components and torque measuring components for the VCM taken along line AA in FIG. [Figure 10] 1 is a graph showing the measurement results of flux for the sintered magnets of Example 2 and Comparative Example 2. [Figure 11] 1 is a graph showing the measurement results of flux for the sintered magnets of Example 3 and Comparative Example 3. [Figure 12] 13 is a graph showing the measurement results of torque in Example 4. [Figure 13] 13 is a graph showing the measurement results of torque in Comparative Example 4. [Figure 14] 1 is a graph showing the rate of change in torque in Example 4 and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of a voice coil motor, magnetic circuit components therefor, and a manufacturing method thereof according to the present invention will be described with reference to the accompanying drawings.
[0018] 1 and 2, a magnetic circuit component 10 for a VCM in this embodiment is mainly composed of a pair of plate-shaped yokes 1, a pair of plate-shaped magnets 2 provided in contact with the inner surfaces of the pair of plate-shaped yokes 1, and a number of pins 3 that secure the pair of plate-shaped yokes 1 together while maintaining a gap between the pair of plate-shaped magnets 2. Note that a VCM can be formed by installing a coil (not shown) in the gap between the pair of plate-shaped magnets 2 of the magnetic circuit component 10.
[0019] 1 and 2, the entire yoke 1 is shown as a flat plate, but the yoke 1 may have some undulations or steps on the outer periphery of the contact surface with the magnet 2. Also, in Fig. 1 and 2, the shape of the magnet 2 is drawn as an arc as an example when the magnetic medium is a circular magnetic disk, but the present invention is not limited to this, and the shape of the magnet 2 may be appropriately made desirable according to the trajectory of the reciprocating motion of the VCM on the magnetic medium, etc. Also, for example, in addition to the pair of plate-like yokes 1, a center yoke or a magnet fixed to the center yoke may be provided in the gap between the pair of plate-like magnets 2.
[0020] Furthermore, the magnetic circuit component for a VCM of the present invention is not limited to the embodiment shown in Figures 1 and 2, and may be, for example, another embodiment shown in Figures 3 and 4. As shown in Figures 3 and 4, a magnetic circuit component 10A for a VCM has a pair of plate-shaped yokes 1A and a pair of plate-shaped magnets 2A provided in contact with the inner surfaces of the pair of plate-shaped yokes 1A, which are similar to those described above, but the support members that secure the pair of plate-shaped yokes 1A together while maintaining a gap between the pair of plate-shaped magnets 2A are multiple struts 3A formed by bending the yoke.
[0021] The material of the yoke 1 may be any conventional material used for the yoke of a VCM, and is not particularly limited, but may be, for example, cold rolled steel plate (SPCC) material, stainless steel material, or the like.
[0022] The plate-shaped magnet 2 is attached to the inner surface of the plate-shaped yoke 1 with an adhesive (not shown). There are no particular limitations on the adhesive, but an adhesive with low outgassing is used to prevent foreign matter from adhering to the actuator, etc. Examples of such adhesives include acrylic and epoxy adhesives.
[0023] The plate-shaped magnet 2 is a rare earth sintered magnet with a coating on its surface. The rare earth sintered magnet has a composition consisting of 28-34 wt% R (R is one or more rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La, and Gd), 2 wt% or less Co, 0.5-2 wt% B, 2 wt% or less of at least one element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu, and Zn as an additive, and the remainder being Fe and unavoidable impurities.
[0024] The surface coating of the rare earth sintered magnet has a multi-layer structure consisting of, in order from the rare earth sintered magnet side, a metal plating layer, and a metal oxide layer and / or a metal nitride layer. The metal plating layer further has a multi-layer structure consisting of, in order from the rare earth sintered magnet side, a copper plating layer and a nickel plating layer. The metal oxide layer and / or metal nitride layer are formed by heat treating the metal plating layer.
[0025] The number of metal plating layers is preferably 2 to 5. The total thickness of the metal plating layers and the metal oxide layers and / or metal nitride layers is preferably in the range of 3 to 80 μm, more preferably 5 to 60 μm. If the total thickness exceeds 80 μm, it will take time and cost, making efficient production impossible and may have a negative effect on the magnetic properties. On the other hand, if the thickness is less than 3 μm, it will be impossible to improve the impact resistance of the sintered magnet body itself, making it impossible to prevent chipping, and furthermore, the metal plating will be prone to unevenness and there will be many pinholes, which may result in insufficient formation of the metal oxide layers and / or metal nitride layers.
[0026] The thickness of the metal oxide layer and / or metal nitride layer is preferably in the range of 0.01 to 2 μm. If the thickness of the metal oxide layer and / or metal nitride layer exceeds 2 μm, it will take time and cost, making efficient production impossible, and may have a negative effect on the magnetic properties. On the other hand, if the thickness is less than 0.01 μm, the action and function of the metal oxide layer and / or metal nitride layer will not be fully exerted. The thickness of the metal oxide layer and / or metal nitride layer can be measured by analyzing the element concentration and chemical bond state in the depth direction of the cross section of the magnet 2 using X-ray photoelectron spectroscopy (XPS).
[0027] By forming a surface coating of a metal plating layer and a metal oxide layer and / or a metal nitride layer on the surface of the rare earth sintered magnet in this way, even if the VCM is exposed to a hydrogen atmosphere for a long period of time inside the housing of a storage device such as an HDD, not only can it be prevented that damage such as chipping or cracking occurs in the pair of magnets 2, but it can also be prevented that the magnetic properties of the pair of magnets 2 will deteriorate due to exposure to hydrogen. Therefore, even if the inside of the housing is filled with hydrogen instead of helium, precise control of the actuator by the VCM can be maintained, and data can be read and written accurately on the magnetic medium.
[0028] The material of the coil used to use this magnetic circuit component for VCM as a VCM may be any conventional material used for VCM coils, and is not particularly limited, but is preferably, for example, copper, etc. The coil is preferably wound around one of the yokes 1 and the magnet 2 so as to be movable.
[0029] Next, a method for manufacturing the magnetic circuit components for the VCM according to the present embodiment will be described. Note that since the magnetic circuit components have already been described, a detailed description will be omitted here.
[0030] The manufacturing method of the magnetic circuit component for a VCM of this embodiment includes the steps of (1) forming a pair of plates made of rare earth sintered magnets having the above composition, (2) plating the surfaces of the pair of plates with copper and then plating nickel on top of that to form a metal plating layer, (3) forming a metal oxide layer and / or metal nitride layer by heat treating the pair of plates with the metal plating layer formed thereon, (4) bonding a pair of yokes to the pair of plates with the metal oxide layer and / or metal nitride layer formed thereon, and (5) fixing the pair of yokes to each other with support members so that the pair of plates bonded to the pair of yokes face each other and so that a gap is maintained between the pair of plates. Each step will be described in detail.
[0031] The process for forming the pair of plates can be carried out by first casting an alloy having the above-mentioned composition, crushing it, and more preferably finely pulverizing it, and then sequentially molding it in a magnetic field, sintering it, and heat treating it to produce a sintered magnet.
[0032] More specifically, the raw material having the above composition is melted by high-frequency melting in a non-oxidizing atmosphere such as argon, and cast. Next, the alloy is coarsely pulverized, and then, although not particularly limited, is finely pulverized to an average particle size of preferably 1 to 10 μm. This coarse pulverization can be performed, for example, in an inert gas atmosphere by a jaw crusher, a Braun mill, a pin mill, hydrogen absorption, or the like. Moreover, fine pulverization can be performed by a wet ball mill or an attritor using alcohol, hexane, or the like as a solvent, a dry ball mill in an inert gas atmosphere, a jet mill using an inert gas stream, or the like.
[0033] Next, the finely pulverized powder is subjected to a magnetic field press, preferably at a pressure of 200 kg / cm, using a magnetic field press capable of applying a magnetic field of 10 kOe or more, particularly 15 kOe or more. 2 More than 2000kg / cm 2 The resulting compression molded body is then sintered in a heat treatment furnace in a high vacuum or in a non-oxidizing gas atmosphere such as argon at 1000 to 1200° C. for 1 to 2 hours.
[0034] Next, a heat treatment is performed in a vacuum or in a non-oxidizing gas atmosphere such as argon at a temperature lower than the sintering temperature, preferably at a temperature of 400 to 700°C, to obtain a sintered magnet. The sintered magnet thus obtained is cut into a pair of plates having a predetermined shape, and the surfaces are polished for finishing. At this time, although there is no particular limitation, it is preferable that the rare earth sintered magnet body is chamfered.
[0035] In the process of forming the metal plating layer, n layers (n is an integer) of metal plating layers are formed on the pair of plates of the rare earth sintered magnet. Here, the more layers of the metal plating layer, the better the corrosion resistance. Therefore, n is selected depending on the corrosion resistance required by the application and other conditions. However, considering the manufacturing cost and efficiency, n=2 to 5. The metal of the metal plating is made of Cu and Ni, and the plating thickness is preferably 3 to 80 μm, particularly 5 to 50 μm. More specifically, it is a multi-layer plating in which Cu is formed in the lower layer and Ni is further formed. As a pretreatment for applying this metal plating, although it is not particularly limited, it is preferable to degrease the pair of plates with an alkali, wash with an acid, and rinse with water. As a method for forming the plating film, although it is not particularly limited, an electrolytic plating method is preferable. In addition, the method for immersing the pair of plates in the plating solution may be either the barrel method or the hook jig method, and is appropriately selected depending on the size and shape of the pair of plates.
[0036] As the electrolytic plating solution, a plating solution of known composition can be used, and plating can be performed under known conditions according to the plating solution, with a plating solution of pH 2 to 12 being particularly preferred. When two or more layers of metals with different compositions are laminated, the corrosion potential of the layer immediately below should be made nobler than that of the uppermost layer, but in a method of controlling the potential by changing the sulfur content in the film, such as in the case of two-layer plating of Ni, the sulfur content of the upper layer should be about 0.03% or less, and the lower layer should contain no sulfur.
[0037] In the step of forming the metal oxide layer and / or metal nitride layer, the pair of plates on which the metal plating layer is formed can be heat-treated in an atmosphere such as air, oxygen partial pressure adjustment, nitrogen, or nitrogen pressure to oxidize or nitride the metal of the metal plating layer to form the metal oxide layer or metal nitride layer. More specifically, when forming the metal oxide layer, it is preferable to perform heat treatment at 200 to 600°C for 3 to 50 hours in an argon, nitrogen, air, or low pressure vacuum atmosphere with an oxygen partial pressure of 10-4 Pa to 50 kPa. The total thickness of the metal plating layer and the metal oxide layer and / or metal nitride layer is in the range of 3 to 80 μm, and the thickness of the metal oxide layer and / or metal nitride layer is 0.01 to 2 μm. The thickness of the metal oxide layer and / or metal nitride layer can be measured by X-ray photoelectron spectroscopy (XPS) as described above.
[0038] In the step of bonding the pair of yokes to the pair of plates, a pair of plates having a metal oxide layer and / or a metal nitride layer formed thereon are bonded to the inner side surfaces of the pair of yokes 1, 1A as shown in Figures 1 to 4. The adhesive used for bonding has been described above, and therefore will not be described here.
[0039] 1 to 4, the process of fixing the pair of yokes together involves, for example, using a plurality of pins 3 as support members or a plurality of pillars 3A formed by bending the yoke, fixing the pair of yokes 1, 1A together so that the pair of plate-like magnets 2, 2A bonded to the pair of plate-like yokes 1, 1A face each other and so that a gap is maintained between the pair of plates. This makes it possible to manufacture magnetic circuit components 10, 10A for a voice coil motor that include a pair of plate-like magnets 2, 2A made of rare earth sintered magnets having a predetermined composition and a predetermined coating on the surface. EXAMPLES
[0040] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0041] [Example 1] First, a magnet alloy was prepared by mixing 29.5% by weight of Nd+Pr, 0.5% by weight of Co, 0.9% by weight of B, and additives of 0.65% total of Al, Cu, Zr, and Ga, with the remainder being Fe. The mixture was melted in an alumina crucible in an argon gas atmosphere in a high-frequency melting furnace and then cast into a mold.
[0042] Next, the magnet alloy was coarsely crushed to about 500 μm or less using a jaw crusher and a Braun mill, and then finely crushed to an average particle size of about 3 μm using a jet mill with a nitrogen gas flow. The obtained finely crushed powder was subjected to a magnetic field press at 1.2 t / cm in a magnetic field of 10 kOe. 2 The resulting compact was sintered in an argon atmosphere at 1,070°C for 2 hours in a heat treatment furnace, then cooled and further heat treated in an argon atmosphere at 600°C for 1 hour to produce a sintered magnet. The resulting sintered magnet was cut into a circular arc plate having the same shape as the magnet for the VCM.
[0043] Then, this circular arc plate was electrolytically plated with Cu (10 μm) and Ni (10 μm) in this order. In this case, a plating bath containing 60 g / L of copper pyrophosphate, 240 g / L of potassium pyrophosphate, and 30 g / L of potassium oxalate was used, and the bath temperature was 40° C., the current density was 1.5 A / dm 2 Then, electrolytic Cu plating was performed using a plating bath adjusted to Ni chloride 40g / L, Ni sulfate 270g / L, and boric acid 30g / L, with a bath temperature of 50°C and a current density of 2.0A / dm 2 Then, the plate was subjected to a heat treatment in air at 350° C. for 10 hours, and then slowly cooled to room temperature to obtain a test sample (Example 1).
[0044] [Comparative Example 1] For comparison, a test sample was obtained in the same manner as in Example 1, except that instead of sequentially applying electrolytic Cu plating (10 μm) and electrolytic Ni plating (10 μm) to the arc-shaped plate and then performing heat treatment in Example 1, electrolytic Ni plating (10 μm) and electrolytic Ni plating (10 μm) were sequentially applied, and then no heat treatment was performed (Comparative Example 1).
[0045] [Hydrogen exposure test] Then, each test sample of Example 1 and Comparative Example 1 was placed in a pressure vessel and exposed to a hydrogen atmosphere (0.29 MPa, 100°C) for 7 days, and the flux (total magnetic flux), demagnetization curve, and torque in the rotation direction of the swing arm of the voice coil motor were measured before hydrogen exposure and after 4, 5, 6, and 7 days of hydrogen exposure, and the appearance of the test sample and the structure of the cross section were observed. The flux and demagnetization curve were measured for two test samples each of Example 1 and Comparative Example 1.
[0046] Flux was measured using a flux meter (Magnet Force Corporation, model number TFM-2000) to measure flux (unit: Wb·T). A coil of 70 μm diameter copper wire × 100 turns was used as the search coil. The flux measurement results of Example 1 and Comparative Example 1 are also shown in FIG. 5.
[0047] The demagnetization curve was obtained by measuring the magnetic properties of the test sample using a vibrating sample magnetometer (manufactured by Riken Denshi Co., Ltd.), including the residual magnetic flux density Br (unit: T), intrinsic coercivity HcJ (unit: kA / m), coercivity HcB (unit: kA / m), and maximum energy product (BH)max (kJ / m 3 ) was measured. Based on these measurement results, a JH curve was obtained by plotting the magnetic field H on the horizontal axis and the magnetization J on the vertical axis. The demagnetization curves (JH curves) of Example 1 and Comparative Example 1 are shown in Fig. 6 and Fig. 7, respectively.
[0048] Torque measurement in the rotational direction of the swing arm was performed by fabricating a magnetic circuit component 10 for VCM using the test sample as the magnet 2 and attaching a torque measurement component 20 to it, as shown in Figures 8 and 9. Note that Figure 9 is a side cross-sectional view of the magnetic circuit component 10 for VCM and the torque measurement component 20 taken along line AA in Figure 8, and Figure 8 is a plan cross-sectional view of them taken along line BB in Figure 9. Note that in Figure 8, the magnet 2 is omitted from the magnetic circuit component 10 for VCM to clarify the drawing. The magnetic circuit component 10 for VCM has already been explained, so explanation will be omitted here.
[0049] The torque measuring component 20 includes a main body 21 having a rotating shaft 23, a swing arm 22 having a through hole on the center line for passing the rotating shaft 23 therethrough and a bifurcated tip, an air-core coil 25 held at the bifurcated tip of the swing arm 22, an angle sensor (not shown) for measuring the angle of the swing arm 22, and a torque sensor (not shown) for measuring the torque in the rotational direction of the swing arm 22. The swing arm 22 is rotatably supported by the rotating shaft 23. An end 24 of the main body 21 opposite to the swing arm 22 has a comb-like shape. The magnetic circuit component 10 for VCM here is a magnetic circuit for VCM in which, after the magnet 2 is attached to the yoke 1, the end surface is magnetized into two poles, with the radial center of the magnet 1 being the center of the neutral zone (the center of the boundary zone of the magnetic poles).
[0050] Torque measurement was performed by rotating the swing arm 22 of the torque measurement component 20 while passing a current through the air-core coil 25 using a constant voltage power supply (not shown), and measuring the torque at each swing arm angle by reading the values of the angle sensor and torque sensor of the torque measurement component 20. Note that during measurement, the angle was defined as 0° when the position of the center line of the swing arm 22 was at the center of the neutral zone of a pair of magnets 2 each magnetized to two poles. During measurement, current was passed in two directions, forward and reverse, and the average of the absolute values was defined as the torque value at that angle.
[0051] The appearance of the test sample was observed visually, and the cross-section structure of the test sample was observed using a scanning electron microscope (manufactured by JEOL Ltd.).
[0052] As a result of observing the appearance of the test samples, no damage such as chipping or cracking was observed in any of the test samples after hydrogen exposure in Example 1. As shown in FIG. 5, the flux of Example 1 was 310×10 -5 The value of Wb / T was maintained even after 7 days had passed since the hydrogen exposure. In addition, as shown in Figure 6, the demagnetization curve (JH curve) maintained the same squareness as before the hydrogen exposure (day 0) even after 7 days had passed since the hydrogen exposure.
[0053] On the other hand, in Comparative Example 1, in which no heat treatment was performed after metal plating, many test samples were used in a hydrogen exposure test, and as a result, after 4 days of hydrogen exposure, 4% of the test samples were found to have damage such as chipping and cracking, after 5 days of hydrogen exposure, 15% of the remaining test samples were found to have damage, after 6 days of hydrogen exposure, 54% of the remaining test samples were found to have damage, and after 7 days of hydrogen exposure, 36% of the remaining test samples were found to have damage. Thus, it was confirmed that the formation of metal oxide by heat treatment after metal plating in Example 1 can prevent damage such as chipping and cracking from occurring in magnets.
[0054] However, the flux of Comparative Example 1 was measured on a test sample that was not damaged, but as shown in FIG. -5 Wb / T, but after 4 days of hydrogen exposure, it was 280-290×10 -5 Wb / T, and after 5 days of hydrogen exposure, the flux was 270-280×10 -5 It had decreased to about Wb / T.
[0055] As for the demagnetization curve (JH curve), even though the magnetic properties were measured for the test specimens without damage in Comparative Example 1, none of the test specimens after hydrogen exposure could maintain the squareness of the test specimens before hydrogen exposure, as shown in FIG. 7. The VCM uses the fact that when a current flows through a coil in the magnetic field of a magnet, a force is generated in the direction perpendicular to both the magnetic field and the current according to Fleming's left-hand rule, to reciprocate the actuator. Since the actuator is precisely controlled by generating a thrust force proportional to the current, the magnetic properties of the magnet deteriorate due to hydrogen exposure as shown in FIG. 7, and if a constant magnetization J cannot be maintained within a certain range of a certain magnetic field H, the actuator cannot be precisely controlled, and data cannot be read or written.
[0056] When the cross-sectional structure of the test sample of Comparative Example 1, which was undamaged 4 to 7 days after hydrogen exposure, was observed, no particular abnormalities were found in the Ni plating layer on the surface or the magnet underneath. Also, when the cross-sectional structure of the test sample of Example 1, which was exposed to hydrogen 4 to 7 days after hydrogen exposure, was observed, no particular abnormalities were found in the metal oxide layer on the surface, the Ni plating layer underneath, the Cu plating layer, or the magnet.
[0057] In addition, instead of the composition of the magnet alloy of Example 1, Example 2 had a composition of Nd+Pr: 28.5% by weight, Dy: 1.0% by weight, Co: 0.5% by weight, B: 0.9% by weight, Al, Cu, Zr, Ga as additives, a total of 0.60%, and the balance Fe, and Example 3 had a composition of Nd+Pr: 33.0% by weight, Co: 1.0% by weight, B: 1.0% by weight, Al, Cu, Zr, Ga as additives, a total of 0.75% by weight, and the balance Fe. In the same manner as in Example 1, electrolytic Cu plating (10 μm) and electrolytic Ni plating (10 μm) were sequentially applied, and then, in Example 2, heat treatment was performed in air under the conditions of 300°C x 20 hours, and in Example 3, 400°C x 5 hours, respectively, to prepare test samples of the magnet alloy. In addition, for comparison, the above magnet alloy was subjected to the same plating treatment as in Comparative Example 1 to obtain test samples of Comparative Example 2 and Comparative Example 3.
[0058] The test samples of Examples 2 and 3 and Comparative Examples 2 and 3 were subjected to the same hydrogen exposure test as above, and flux measurements were performed. The flux measurement results of Example 2 and Comparative Example 2 are shown in Figure 10, and the flux measurement results of Example 3 and Comparative Example 3 are shown in Figure 11. As shown in Figures 10 and 11, the results of the compositions of the magnet alloys of Examples 2 and 3 were similar to those of the magnet alloy of Example 1.
[0059] Furthermore, the thickness of the metal oxide layer on the surface of the test sample of Example 1 was measured using an X-ray photoelectron spectrometer (AXIS-HSI, manufactured by Shimadzu Kratos) and was found to be about 0.05 μm.
[0060] A magnetic circuit component for a VCM was manufactured using a test sample (Example 4) prepared using the same procedure as in Example 1, in which a pair of rare earth magnets were magnetized with two poles each in a 3 T magnetic field, and the torque measurement described above was performed. The hydrogen exposure conditions for the test samples were also the same as in Example 1, and samples were manufactured and measured using each exposure condition. The results are shown in Figure 12. As shown in Figure 12, at all angles, the torque was maintained the same as before hydrogen exposure (day 0) even after 7 days had passed since hydrogen exposure.
[0061] A test sample (Comparative Example 4) was prepared using the same procedure as Comparative Example 1, and a pair of rare earth magnets were magnetized with two poles in a magnetic field of 3 T. Torque measurements were carried out in the same manner as in Example 4. The results are shown in Figure 13. As shown in Figure 13, in Comparative Example 4, the torque decreased at all angles depending on the exposure time in hydrogen.
[0062] In order to analyze the maintenance and decrease of torque in more detail, the maximum torque value at each exposure time was obtained from the torque measurement results of Example 4 and Comparative Example 4 described above, and the rate of change of the maximum torque value before and after exposure (pre-exposure being set at 100) was calculated. The results are shown in FIG. 14. As shown in FIG. 14, in Comparative Example 4, the torque decreased with increasing exposure time, and a decrease of 4.4% was observed after 7 days of exposure. On the other hand, in Example 4, no decrease in torque was observed.
[0063] In this way, it was confirmed that by metal plating a magnet and then performing a heat treatment to form a metal oxide on the surface, it is possible to reliably prevent damage such as chipping and cracking caused by hydrogen exposure, but it was also found that metal plating alone can suppress damage such as chipping and cracking caused by hydrogen exposure to a certain extent. However, in the comparative example where only metal plating was used, it was confirmed that even if such damage did not occur, the magnetic properties of the magnet deteriorated and it was not suitable for use as a magnet for VCM. [Explanation of symbols]
[0064] 1, 1A York 2, 2A magnet 3-pin 3A Bent Yoke Support Magnetic circuit components for 10, 10A voice coil motors (VCM) 20 Torque measuring parts 22 Swingarm 23 Rotation axis 25 Air core coil
Claims
1. A magnetic circuit component for a voice coil motor, comprising: a pair of yokes; a pair of magnets provided in contact with inner surfaces of the pair of yokes, respectively; and a support member that fixes the pair of yokes together while maintaining a gap between the pair of magnets, The magnet is a rare earth sintered magnet having a coating on its surface, the rare earth sintered magnet has a composition consisting of 28 to 34 weight % R (R is one or more rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La, and Gd), 2 weight % or less Co, 0.5 to 2 weight % B, 2 weight % or less of at least one element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu, and Zn as an additive, and the balance being Fe and unavoidable impurities; a magnetic circuit component for a voice coil motor, wherein the coating has a multi-layer structure consisting of, in order from the rare earth sintered magnet side, a metal plating layer and a metal oxide layer and / or a metal nitride layer, the metal plating layer further has a multi-layer structure consisting of, in order from the rare earth sintered magnet side, a copper plating layer and a nickel plating layer, the total thickness of the metal plating layer and the metal oxide layer and / or metal nitride layer is in the range of 3 to 80 μm, and the metal oxide layer and / or metal nitride layer has a thickness in the range of 0.01 to 2 μm.
2. 2. A voice coil motor comprising: a magnetic circuit component for a voice coil motor according to claim 1; and a coil located in the gap between the pair of magnets.
3. forming a pair of plates made of rare earth sintered magnets having a composition consisting of 28 to 34 weight % R (R is one or more rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La, and Gd), 2 weight % or less Co, 0.5 to 2 weight % B, 2 weight % or less of at least one element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu, and Zn as an additive, and the balance being Fe and unavoidable impurities; a step of plating the surfaces of the pair of plates with copper and then plating the surfaces with nickel to form a metal plating layer; a step of heat-treating the pair of plates on which the metal plating layer is formed to oxidize and / or nitride the metal of the metal plating layer to form a metal oxide layer and / or a metal nitride layer, in which the total thickness of the metal plating layer and the metal oxide layer and / or the metal nitride layer is in the range of 3 to 80 μm, and the thickness of the metal oxide layer and / or the metal nitride layer is in the range of 0.01 to 2 μm; a step of bonding a pair of yokes to the pair of plates on which the metal oxide layer and / or metal nitride layer is formed, respectively; a step of fixing the pair of yokes to each other with a support member so that the pair of plates bonded to the pair of yokes face each other and a gap is maintained between the pair of plates; A method for manufacturing a magnetic circuit component for a voice coil motor comprising the steps of:
Citation Information
Patent Citations
Permanent magnet material
JP2001230106A
Permanent magnet material
JP2001250707A
Permanent magnet material
JP2001257112A
Rotary disk type storage device
JP2005327407A
Permanent magnet member for voice coil motor, and voice coil motor
JP2012142049A